COPING MANUFACTURED TECHNIQUE OF SPINELL SLIP CAST ALL CERAMIC BY CONVENTIONAL METHODS AND CAD/CAM - Hidayatin, Insani; Indiani, Sri Redjeki; Ratwita, Rr. Dwiyanti Feriana (Journal of Vocational Health Studies, 2019)
Background: Ceramic restorations is divided into two kindsnamelyPorcelain Fused to Metal (PFM) and all-ceramic restorations. In ceram spinell is one of the materials needed for manufacturing anterior coping of all ceramic which has better aesthetic than in other in ceram. Methods which have been done are Conventional Slip Cast by application of spinell paste on refractory die manually and CAD/CAM computer-based technique. The difference of mentioned previously methods is few step-in slips cast methods can be performed only by one step CAD/CAM methods. Purpose: To discover the differences between Conventional Slip Cast methods and CAD/ CAM methods. Review: Application of CAD/CAM methods has few advantages compared to conventional methods. Since few step-in conventional methods can be performed only one step in CAD/CAM methods. Conclusion: In order to shorten the time in manufacturing spinell all-ceramic, the dental technician may use CAD/CAM methods. Few advantages of CAD/CAM methods compare to slip cast methods are not necessary to do die to block out, die duplication, wetting agent spraying, vitasonic and ultrasonic usage, giving border by ink pen for determining application border, preparing spinell paste for coping application. Those steps all can be performed only by scanning, design, and milling by CAD/CAM methods. Besides that, coping result produced by CAD/ CAM methods has good accuracy due to spinell block utilization which has better homogenous composition.